Synthesis of Naturally Racemic Marilines B & C through Multicomponent Reactions Involving ortho-Quinone Methides and Various Nitrogen Nucleophiles - Wong, Yuk Fai; Pettus, Thomas R. R. (Synthesis, 2023)
Herein, we report the first total synthesis of (±)-marilines B and C, as well as a failed approach to (±)-mariline A, by using our recently developed multicomponent reaction method, which involves the interception of ortho-quinone methides with various nitrogen nucleophiles to allow easy assembly of various benzylic amine cores with diverse substituents.
Keywords: ortho-quinone methides; marilines; imines; dihydrooxazoles; anilines; isoindolin-1-ones; phthalimidines; salicylaldehydes